Effect of a universal anxiety prevention programme (FRIENDS) on children's academic performance: results from a randomised controlled trial. (18th July 2016) - Skryabina, Elena; Taylor, Gordon; Stallard, Paul
Abstract : Background: Evaluations of school‐based anxiety prevention programmes have reported improvements in psychological functioning although little is known about their effect upon educational outcomes. Methods: One thousand three hundred and sixty‐two children from 40 primary schools in England took part in the randomised controlled trial, Preventing Anxiety in Children through Education in Schools. The trial investigated the effectiveness of a universal school‐based cognitive behaviour therapy prevention programme, FRIENDS, delivered by health care staff or school staff compared with usual personal, social, health and education (PSHE) lessons. Self‐report psychological outcomes and educational attainment on national standardised attainment tests in reading, writing and maths were collected 12 months postintervention. Analysis was performed at individual level using multivariable mixed effect models controlling for gender, type of intervention and school effect. Registered trial: ISRCTN: 23563048. Results: At 12 months, anxiety reduced in the health‐led FRIENDS group compared to school‐led FRIENDS and PSHE. There were no between‐group differences in academic performance regardless of gender, deprivation, ethnicity and additional educational needs. Conclusions: School‐based mental health interventions should assess psychological and educational outcomes. Further research should directly compare the effects of interventions led by health and school staff.